Reconstruction of Self in a Post- Colonial world: Retrieval of Identity in Yann Martel’s Life of Pi: Exploring the impact of colonial discourse and post-colonial reconstruction on identity retrieval in Yann Martel’s Life of Pi (Journal of Advances and Scholarly Researches in Allied Education, 2018)
For hundreds of years, colonial discourse had been taking a shot at etching the space between inflexible polarities developed by the western bits of knowledge. Human or animal, civilized or savage, man or nature, hunter or hunted and the norm or the other are among such doubles which contributed in solidifying an expansive vision of progress its highlights, principles and prerequisites. Building up a conspicuous difference among human and creatures, provincial introduction went for debasing the native in the colonized nations. In this manner, colonizing realms legitimized the killing of the native, since they were considered a long way from being human as indicated by the western viewpoint.